Deskripsi Kesulitan Belajar Matematika Siswa Ditinjau dari Gaya Kognitif dengan Model Pembelajaran Think Pair Share (TPS) pada Siswa Kelas VIII SMP Batik Surakarta - Anfus, Achmad Syaeful Nur, Muhammad Noor Kholid, S.Pd., M.Pd (2017)
This research is aimed to describe the difficulty of learning mathematic viewed from cognitive style using learning model of Think Pair Share (TPS). This research belongs to qualitative research. Subjects of the research consist of four subjects, 2 subjects have cognitive style of field independent and 2 other subjects have cognitive style of Field Dependent in the class VIII-G of SMP Batik Surakarta. Technique of collecting data uses instrument technique of GEFT to know students' cognitive style, observation technique in the class VIII-G of SMP Batik Surakarta, test technique to know the students' difficulty of learning mathematics, and interview technique was conducted to students who have difficulty on learning mathematic that based on students' cognitive style. Test was conducted after learning activity for 3 meetings. It was conducted on each meeting on the material of geometry in sub-material of cube, cuboid, prism, and pyramid using learning model of Think Pair Share (TPS). The result of test and interview is analyzed by using 4 indicators of the difficulty of learning mathematics from Lerner, namely: (1) the interruption of spatial relation, (2) preservation (3) the difficulty on recognizing and understanding symbol and (4) the difficulty on language and reading. The result of the research can be shown as follows; students who have cognitive style of Field Dependent tend to have difficulty on a) interruption of spatial relation, ie students have the difficulty in writting unit of width and volume and have difficulty in differentiating or determine the formula of 3D shape; b) the difficulty on recognizing and understanding symbols ie students have difficulty in using mathematical symbols, while Field Inependent tend to have difficulty : a) preservation, ie students have difficulty in operating the problems with the exixtence of interference attached to a particular object ; b) the dificulty on languange and reading ie students have dificulty on solve mathematic problems form story problems.